Epidemiology of Neonatal Stroke: A Population-Based Study. (1st June 2016) - Clive, B; Vincer, M; Ahmad, T; Khan, N; Kuhle, S; Afifi, J; El-Naggar, W
Abstract: BACKGROUND: Neonatal stroke (NS) is a known cause of cerebral palsy, epilepsy and cognitive deficits in up to 50% of patients. Understanding its epidemiology can help in early identification of affected patients and in improving outcomes. OBJECTIVES: To obtain population-based data on the incidence, clinical presentation, treatment, imaging features and outcomes of patients with all types of neonatal stroke. DESIGN/METHODS: Full term neonates born to mothers living in Nova Scotia between 2007 and 2013 and diagnosed with NS were identified through the province's Perinatal Follow-up Program Database. Neonates with significant congenital anomalies or hypoxic ischemic encephalopathy were excluded. Perinatal data and neonatal course were reviewed. Neurodevelopmental outcomes were assessed at 18 months of age using the standardized cognitive adaptive test/clinical linguistic auditory milestone scale (CAT/CLAMS). RESULTS: Twenty-nine neonates (47 per 100, 000 live births) with NS were identified during the study period. The mean gestational age was 39±1 weeks and mean birth weight was 3278±579 g. In twenty-two (76%), NS was due to neonatal arterial ischemic stroke (NAIS), 2 (7%) to cerebral sinovenous thrombosis, and 5 (17%) to intracerebral hemorrhage. Seizures were the most common presenting sign. [table] The median length of stay in hospital was 7 days (4-21). At 18 months of age, only 2 patients (7%) were found to have cerebral palsy and one had epilepsy (3%). CONCLUSION: The majority of patients with NS had NAIS and presented with seizures on the first day of life. The incidence of NS in Nova Scotia is higher than reported in the literature, however the neurodevelop-mental outcomes are better.